Characteristics of High- and Low-Efficiency Hospitals. (August 2018) - Rosko, Michael; Wong, Herbert S.; Mutter, Ryan
We compared performance, operating characteristics, and market environments of low- and high-efficiency hospitals in the 37 states that supplied inpatient data to the Healthcare Cost and Utilization Project from 2006 to 2010. Hospital cost-inefficiency estimates using stochastic frontier analysis were generated. Hospitals were then grouped into the 100 most- and 100 least-efficient hospitals for subsequent analysis. Compared with the least efficient hospitals, high-efficiency hospitals tended to have lower average costs, higher labor productivity, and higher profit margins. The most efficient hospitals tended to be nonteaching, investor-owned, and members of multihospital systems. Hospitals in the high-efficiency group were located in areas with lower health maintenance organization penetration and less competition, and they had a higher share of Medicaid and Medicare admissions. Results of the analysis suggest there are opportunities for public policies to support improved efficiency in the hospital sector.